Laser ablation for mesial temporal lobe epilepsy: Surgical and cognitive outcomes with and without mesial temporal sclerosis. (12th June 2018) - Donos, Cristian; Breier, Joshua; Friedman, Elliott; Rollo, Patrick; Johnson, Jessica; Moss, Lauren; Thompson, Stephen; Thomas, Melissa; Hope, Omotola; Slater, Jeremy; Tandon, Nitin
Summary: Objectives: Laser interstitial thermal therapy (LITT) is a minimally invasive surgical technique for focal epilepsy. A major appeal of LITT is that it may result in fewer cognitive deficits, especially when targeting dominant hemisphere mesial temporal lobe (MTL) epilepsy. To evaluate this, as well as to determine seizure outcomes following LITT, we evaluated the relationships between ablation volumes and surgical or cognitive outcomes in 43 consecutive patients undergoing LITT for MTL epilepsy. Methods: All patients underwent unilateral LITT targeting mesial temporal structures. FreeSurfer software was used to derive cortical and subcortical segmentation of the brain (especially subregions of the MTL) using preoperative magnetic resonance imaging (MRI). Ablation volumes were outlined using a postablation T1‐contrasted MRI. The percentages of the amygdala, hippocampus, and entorhinal cortex ablated were quantified objectively. The volumetric measures were regressed against changes in neuropsychological performance before and after surgery, Results: A median of 73.7% of amygdala, 70.9% of hippocampus, and 28.3% of entorhinal cortex was ablated. Engel class I surgical outcome was obtained in 79.5% and 67.4% of the 43 patients at 6 and 20.3 months of follow‐up, respectively. No significant differences in surgical outcomes were found across patient subgroups (hemispheric dominance, hippocampal sclerosis, or need for intracranial evaluation). Furthermore, no significant differences in volumes ablated were found between patients with Engel class IA vs Engel class II‐IV outcomes. In patients undergoing LITT in the dominant hemisphere, a decline in verbal and narrative memory, but not in naming function was noted. Significance: Seizure‐free outcomes following LITT may be comparable in carefully selected patients with and without MTS, and these outcomes are comparable with outcomes following microsurgical resection. Failures may result from non‐mesial components of the epileptogenic network that are not affected by LITT. Cognitive declines following MTL‐LITT are modest, and principally affect memory processes.